Association between serum neurofilament light chain levels and chronic kidney disease: a cross-sectional population-based study from the National Health and Nutrition Examination Survey (2013–2014 cycle) - Jian-De Lu; Kaisaierjiang Kadier; Diliyaer Dilixiati; Bingzhang Qiao; Renaguli Nuer; Abudureheman Zebibula; Mulati Rexiati; Kai Li; ShuiXue Li (Renal Failure)
Background The relationships of serum neurofilament light chain (NfL) levels with chronic kidney disease (CKD) and renal function indicators remain controversial, and comprehensive studies with large sample sizes are lacking.Methods In total, 2,051 participants aged 20 to 75 years were identified from the National Health and Nutrition Examination Survey (2013-2014 cycle). Logistic regression models were used to assess the associations between serum NfL levels and CKD, whereas multivariate linear models were used to investigate the relationships between serum NfL levels and two kidney function indicators, namely, estimated glomerular filtration rate (eGFR) and urinary albumin–creatinine ratio (UACR). Adjustments were made to account for potential confounding variables in the analysis. Subgroup analyses stratified by age and sex were conducted. When sNfL is incorporated into the model as continuous variables, a log transformation is applied.Results The present study included a cohort of 2,051 individuals ranging in age from 20 to 75 years. After covariate adjustment, multivariable logistic regression revealed a significant association between high serum NfL levels and an increased prevalence of CKD (OR 1.60; 95% CI 1.40–1.82; p < 0.0001), which remained significant when analyzed by quartiles (p for trend <0.0001). There was a statistically significant inverse correlation between the serum NfL level and the eGFR (β=-6.34; 95% CI −8.32 to −4.37; p < 0.0001), as well as a positive correlation between the serum NfL level and the UACR (β = 84.67; 95% CI 19.52-149.83; p < 0.0001). Furthermore, when stratified by age, there were significant interactions of serum NfL levels with CKD, the eGFR, and the UACR (p for interaction = 0.008, 0.016, and 0.020, respectively).Conclusion Serum NfL levels are positively associated with the prevalence of CKD and the UACR but negatively correlated with the eGFR, particularly in older patients.